Towards Optimal Wind Power Plant Connecting Line Dimmensioning - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2017)
The integration of wind power into power systems has economic components that must be considered. In particular, the line connecting one the power plant with the electric system may present tradeoffs that needs to be analyzed. On one hand, the line can be dimensioned to carry the maximum capacity of the wind power plant; if the occurrence of maximum output from the resource has low probability, the line will be a significant part of the time underutilized. On the other hand, if the line is dimensioned with a capacity lower than the maximum output of the wind power plant, some energy generation will be curtailed. This work models the tradeoff between line underutilization and energy curtailment in terms of the line cost per unit of capacity, a valorization of energy curtailment, statistical modelling of the wind resource and models of the wind power plant. A method to find a cost-effective line dimension is presented. The challenges of a more systematic approach are also presented. © 2017 IEEE.